Protocol for a randomised clinical trial of multimodal postconcussion symptom treatment and recovery: the Concussion Essentials study. Issue 2 (11th February 2021) - Anderson, Vicki; Rausa, Vanessa C; Anderson, Nicholas; Parkin, Georgia; Clarke, Cathriona; Davies, Katie; McKinlay, Audrey; Crichton, Ali; Davis, Gavin A; Dalziel, Kim; Dunne, Kevin; Barnett, Peter; et al.
Abstract : Introduction: While most children recover from a concussion shortly after injury, approximately 30% experience persistent postconcussive symptoms (pPCS) beyond 1-month postinjury. Existing research into the treatment of pPCS have evaluated unimodal approaches, despite evidence suggesting that pPCS likely represent an interaction across various symptom clusters. The primary aim of this study is to evaluate the effectiveness of a multimodal, symptom-tailored intervention to accelerate symptom recovery and increase the proportion of children with resolved symptoms at 3 months postconcussion. Methods and analysis: In this open-label, assessor-blinded, randomised clinical trial, children with concussion aged 8–18 years will be recruited from The Royal Children's Hospital (The RCH) emergency department, or referred by a clinician, within 17 days of initial injury. Based on parent ratings of their child's PCS at ~10 days postinjury, symptomatic children (≥2 symptoms at least 1-point above those endorsed preinjury) will undergo a baseline assessment at 3 weeks postinjury and randomised into either Concussion Essentials (CE, n=108), a multimodal, interdisciplinary delivered, symptom-tailored treatment involving physiotherapy, psychology and education, or usual care (UC, n=108) study arms. CE participants will receive 1 hour of intervention each week, for up to 8 weeks or until pPCS resolve. A postprogramme assessment will be conducted at 3 months postinjury for all participants. Effectiveness of the CE intervention will be determined by the proportion of participants for whom pPCS have resolved at the postprogramme assessment (primary outcome) relative to the UC group. Secondary outcome analyses will examine whether children receiving CE are more likely to demonstrate resolution of pPCS, earlier return to normal activity, higher quality of life and a lower rate of utilisation of health services, compared with the UC group. Ethics and dissemination: Ethics were approved by The RCH Human Research Ethics Committee (HREC: 37100). Parent, and for mature minors, participant consent, will be obtained prior to commencement of the trial. Study results will be disseminated at international conferences and international peer-reviewed journals. Trial registration number: ACTRN12617000418370; pre-results.